A capric–palmitic–stearic acid ternary eutectic mixture/expanded graphite composite phase change material for thermal energy storage. (August 2016) - Zhang, Hua; Gao, Xuenong; Chen, Caixing; Xu, Tao; Fang, Yutang; Zhang, Zhengguo
Abstract: This paper demonstrated a capric acid–palmitic acid–stearic acid ternary eutectic mixture/expanded graphite (CA–PA–SA/EG) composite phase change material (PCM) for low-temperature heat storage. The CA–PA–SA ternary eutectic mixture with a mass ratio of CA:PA:SA = 79.3:14.7:6.0 was prepared firstly, and its mass ratio in the CA–PA–SA/EG composite can reach as high as 90%. The melting and freezing temperatures of CA–PA–SA/EG composite were 21.33 °C and 19.01 °C, and the corresponding latent heat were 131.7 kJ kg −1 and 127.2 kJ kg −1 . The CA–PA–SA/EG composite powders can be formed into round blocks by dry pressing easily, with much higher thermal conductivity than CA–PA–SA. Thermal performance test showed that the increasing thermal conductivity of CA–PA–SA could obviously decrease the melting/cooling time. Thermal property characterizations after 500 heating/cooling cycles test indicated that CA–PA–SA/EG composite PCM had excellent thermal reliability. Based on all these results, CA–PA–SA/EG composite PCM is a promising material for low-temperature thermal energy storage applications.